Determinants of First‐Line Nurse Managers’ Span of Control: A Delphi Study - Boned-Galán, Ángel; López-Ibort, Nieves; Gil-Lacruz, Ana I.; Gascón-Catalán, Ana (Journal of nursing management, 2024)
Aims: The main goal of this research is to identify, through expert consensus, the key factors that determine the span of control (SOC) of first‐line nurse managers (FLNMs) in the Spanish healthcare system. Background: The SOC is a management concept which has usually been defined as the number of subordinates reporting to a superior. In nursing, however, it is much more complex. This complexity is shaped by various factors related to patients, healthcare professionals and organisational structures. Nursing leaders must thoroughly consider these factors and their determinants, which necessitate a comprehensive assessment. Given the significant impact an inadequate SOC can have on patients, professionals and the organisation, it would be beneficial to address this issue. In nursing, studies on this subject are practically nonexistent and focus solely on the number of subordinates, highlighting the need for research in this area. Methods: Between September and December 2022, a Delphi study was conducted. Forty‐five experts were invited to participate. The study involved nurse administrators, FLNMs, university professors, renowned researchers and other non–health professionals related to health management. The participants completed an online survey over three phases. Factor analysis was performed on the items for which consensus was reached. The jamovi software version 2.3.15 was used for data analysis. Results: A total of 35 experts participated in at least one of the three phases of the Delphi study. Following a comprehensive analysis of the identified factors, a consensus was reached on 31 of them. These were subsequently grouped into four categories: unit category (16 items, including complexity, resource management, conflicts and protocolisation and monitoring of activities), professional category (five items: number of staff, staffing stability and skill level and diversity of staff), FLNM category (four items: autonomy, experience and education and leadership style) and organisation category (six items: digitisation and information systems, education, research and implementation evidence‐based practice and performing guards). Conclusions: Our research shows a high degree of consensus amongst participants in identifying the determinants and degree of relevance of SOC‐related aspects. Although SOC is not currently assessed, all stakeholders agree that there are a large number of variables that should be considered when appointing a FLNM. Implications for Nurse Managers: Nursing managers can better assess the health of the organisation and improve performance by understanding the factors that influence the SOC of FLNMs. Due to the lack of previous studies, understanding these factors will allow the development of methods and tools tailored to the characteristics of different health systems.